Exploring the relationship between craniovertebral angle, hand grip strength and handwriting performance in students - K. P., Rajeetha; Pinto, Royline F. (International Journal of Research in Medical Sciences, 2025)
Background: With the increasing reliance on mobile phones for communication, gaming, and internet use, musculoskeletal issues have become more prevalent, especially among students. Prolonged neck flexion, often associated with forward head posture (FHP), may compromise upper extremity function. Hand grip strength is considered a reliable indicator of upper limb integrity, while handwriting performance reflects fine motor coordination both potentially influenced by postural alignment. This study aimed to examine the relationship between craniovertebral angle (CVA), handwriting performance with hand grip strength among students. Methods: An observational study was carried out over a 12-month period (June 2023–May 2024) at a tertiary care hospital in Southern Karnataka. A total of 77 students participated. CVA was measured using digital photogrammetry, hand grip strength with a handheld dynamometer, and handwriting performance through standardized writing tasks. Statistical analysis, including Pearson’s correlation, was conducted using statistical package for the social sciences (SPSS) version 21.0 to evaluate the relationships among the variables. Results: The analysis found a weak, negative correlation between grip strength and handwriting (r=-0.06, p=0.606), indicating a lack of statistical significance. There was no significant correlation between CVA and hand grip strength, nor between hand grip strength and handwriting performance. Conclusion: The findings suggest that in this student population, there is no significant association between craniovertebral angle, hand grip strength, and handwriting performance. However, generalizability is limited due to the homogeneous age group and restricted sample diversity.